A Mother’s Involvement in Preserving Patriarchal Power in Anita Desai’s Fasting, Feasting - Maharani, Elizabeth Ratih; Rosiandani, Ni Luh Putu (Journal of Language and Literature, 2016)
The issue of women’s oppression is an actual issue which provokes endless discussion. This issue is the domain of feminist’s struggle until now. There are many theories of feminism in literature. This article employs psychoanalytic feminism approach to examine the relation between women’s oppression and women's psyche to finally reveal that a mother (Mama) is involved in preserving the power of patriarchy in the family through her typical treatments toward her daughters (Uma and Aruna). Three conclusions can be drawn. Firstly, Mama is depicted as a narrow-minded, insecure, and status-oriented woman. Uma is an alienated, inferior and curious daughter. Aruna is a superior, status-oriented, and beauty-addicted daughter. Secondly, Mama’s treatment reflects patriarchal values. She prioritizes her son to get nutritious food and qualified education. Mama burdens her daughters with great responsibilities to take care of the house, gives them less freedom for selfexpression, and teaches them that women’s self-worth is determined by their physical attractiveness. Thirdly, there are two factors underlying Mama’s involvement in preserving the power of patriarchy. The first factor is the influence of her mother who made distinctive treatments based on gender toward her children. The second factor is the influence of tradition that addresses child-rearing responsibilities to mothers. Fathers only set the rules, they do not participate in this duty. Mama passes this role down to her daughters. As a result, she is involved in preserving patriarchal power. Keywords: patriarchal power, psychoalanytic feminism, Anita Desai